SEJARAH LITURGI GEREJA KONSTANTINOPEL - Anthony, Christian (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2024)
This research answers the question of how the history and pattern of the Liturgy of the Church of Constantinople is, because the Liturgy of the Church of Constantinople has become a patron for all churches in the Roman empire which are still preserved today. This research is a literature study based on historical qualitative research methods. Researchers investigated many sources, both primary and secondary, to obtain a mature theoretical study as a reference for solving the history and pattern of the Liturgy of the Church of Constantinople. The results of this study are the Liturgy of James is the first liturgy used in the Church of Constantinople, followed by the Liturgy of Basilius the Great and the last is the Liturgy of John Chrysostom, the three liturgies are divided into three patterns, namely Proskomidi worship (Preparation), Liturgy of Catechumens and Liturgy of the Faithful.